A precinct too far: Turnout and voting costs - Cantoni, Enrico (American Economic Journal: Applied Economics)
I study the effects of voting costs$1 (Bspecifically, distance to polling location$1 (Busing geographic discontinuities. Opposite sides of boundaries between voting precincts are observationally identical, except for their assigned polling locations. This discontinuous assignment produces sharp changes in voters' travel distance to cast their ballots. In nine municipalities in Massachusetts and Minnesota, a 1 standard deviation (0.245 mile) increase in distance reduces ballots cast by 2 to 5 percent across four elections. During non-presidential elections, effects are three times larger in high-minority areas than in low-minority areas. Finally, I simulate the impact of various counterfactual assignments of voters to polling places.s
Keywords: Voting